2015
DOI: 10.1037/a0036720
|View full text |Cite
|
Sign up to set email alerts
|

Interreligious contact, attitudes, and stereotypes: A study of five religious groups in Canada.

Abstract: The rich religious diversity in Canada provides a particularly relevant context for the study of interreligious relations. This study analyses the stereotypes of 5 religious groups (Christians, Hindus, Jews, Muslims, and Sikhs) among a sample of undergraduate students (N ϭ 152) in Canada. It also examines the relationship between intergroup contact, knowledge, and attitudes toward these religious groups. Open-ended response methodology was used to elicit participants' perceptions of the characteristics of targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
3
15
1
Order By: Relevance
“…In line with previous work, I believed the common stereotypes associated with Christians would be: religious, good, honest, caring, friendly, loving, judgmental, and ignorant (Zafar & Ross, 2015). Also in line with previous work, I believed the common stereotypes associated with Muslims would be: religious, pray, untrustworthy, violent, terrorist, strict, bad, and good (Sides & Gross, 2013;Zafar & Ross, 2015).…”
Section: Studysupporting
confidence: 83%
“…In line with previous work, I believed the common stereotypes associated with Christians would be: religious, good, honest, caring, friendly, loving, judgmental, and ignorant (Zafar & Ross, 2015). Also in line with previous work, I believed the common stereotypes associated with Muslims would be: religious, pray, untrustworthy, violent, terrorist, strict, bad, and good (Sides & Gross, 2013;Zafar & Ross, 2015).…”
Section: Studysupporting
confidence: 83%
“…Guimond and colleagues (2013) similarly find lower levels of anti-Muslim prejudice in Canada compared to Britain, Germany and the US. At the same time, other research (based on a student sample) has found that Muslims are rated more negatively than other religious groups in Canada (Zafar and Ross, 2015).…”
Section: Attitudes Toward Muslims In Canadian and Comparative Perspecmentioning
confidence: 80%
“…Such issues are not, however, unique to Canada; rather, they are a salient political issue in many Western democracies (Savelkoul et al, 2012; Wike and Grim, 2010). Research focusing on the Canadian case, however, is limited (but see Harell et al, 2012; O'Neill et al, 2015; Roach, 2009; Wright et al, 2017; Zafar and Ross, 2015). Further, I take the position that research exploring the dynamics of majority–Muslim relations in Canada—written for a Canadian audience, as well as those interested in Canada—is an important endeavour (Noël, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Arab youth have reported enhanced acculturative stress levels, challenges in developing their identity, and difficulty establishing peer relationships (Britto & Amer, 2007;Daniel,2013;Shryock & Howell, 2003;Wannas-Jones, 2003;Wrobel, Farrag, & Hymes, 2009). Arab youth shared that one factor to elevated acculturative stress was the negative media portrayals of Arabs and Islam (Awad, 2010;Zafar & Ross, 2015).In the correspondence with Naeem on social justice and full potential achievement, he shares that he fears that the media image would be an adopted response to his attempts to advance professionally and integrate more successfully herein Canada. While he feels that he is generally welcomed here, he senses that some community members may have preconceived images of him because of his background.…”
Section: Social Justice In the Perspective Of Newcomer Youthmentioning
confidence: 99%